A C126R de novo Mutation in CYBB Leads to X-linked Chronic Granulomatous Disease With Recurrent Pneumonia and BCGitis - de Albuquerque, Jose Antonio Tavares; de Oliveira Junior, Edgar Borges; Zurro, Nuria Bengala; Vendramini, Paola; Ishizuka, Edson Kiyotaka; Borgli, Daniela de Souza Paiva; de Souza, Monica Soares; Condino-Neto, Antonio (Frontiers in Pediatrics, 2018)
Chronic granulomatous disease (CGD) is an innate immune deficiency of phagocytic cells caused by mutations that affect components of the NADPH oxidase system, with resulting impairment in reactive oxygen species production. Patients with CGD are susceptible to recurrent infections and hyperinflammatory responses. Mutations in CYBB lead to the X-linked form of CGD and are responsible for ~ 70% of cases. In this study, we report the case of a 2.5-year-old male patient with recurrent pneumonia and Bacillus Calmette-Guérin infection (BCGitis). As his first clinical manifestation, he presented with bullous impetigo at 18 days of age, which was followed by recurrent pneumonia and regional BCGitis. Genetic analysis revealed a de novo mutation in exon 5 of the CYBB gene: a single-nucleotide substitution, c.376T > C, leading to a C126R change.